Effect of physicochemical activation on CO2 adsorption of activated porous carbon derived from pine sawdust - Himanshu Patel; Haftom Weldekidan; Amar Mohanty; Manjusri Misra (Carbon Capture Science & Technology, 2023)
The study reports on cost-effective and novel method for synthesis of activated porous carbon (APC) suitable for post-combustion CO2 capture. Inexpensive and abundant pine sawdust was utilized as a precursor. A hybrid synthesis protocol of physicochemical activation utilizing KOH + CO2 as activating agents was proposed. Effectiveness of APC derived via physicochemical activation was compared with that derived via chemical (only KOH) and physical (only CO2) activation. Also, the effect of carbonization condition on APC performance was investigated. Yield of APC (from precursor to final product) ranged within 20–24 wt.%. The maximum BET surface area of 2216 m2/g and the maximum CO2 adsorption capacity of 6.35 mmol/g at 0 °C/1 bar, 3.82 mmol/g at 25 °C/1 bar and 2.81 mmol/g at 40 °C/1 bar was obtained. Following the ideal adsorbed solution theory, CO2/N2 selectivity was computed at 0 °C, 25 °C and 40 °C and found to be within 10–19. For all the APCs, the isosteric heat of adsorption < 40 kJ/mol indicated physisorption as dominating mechanism for CO2 adsorption. Even after five consecutive adsorption-desorption cycles, multi-cyclic recyclability > 99.5% was observed.